2009
DOI: 10.1097/jac.0b013e31819940f7
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Strategy Based on Pay-Per-Performance to Improve Quality of Care of Family Practitioners in Argentina

Abstract: Pay-for-performance has become increasingly common to complement physician reimbursement. We designed a quality framework to measure family physicians' performance in a managed care setting in Buenos Aires. We aimed to assess the effectiveness of a multimodal intervention based on pay-for-performance, teamwork, continuous education, and audit and feedback to improve quality. After 2 years, a significant improvement was observed in most of the indicators measuring clinical effectiveness and some improvements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
1
12
0
4
Order By: Relevance
“…Once the upper limit of P4P indicators were achieved, practitioners and medical institutions can acquire the corresponding payment, then spare no more effort to enhance the quality of medical care continuously, suggesting a comprehensively modest improvement in part consistent with previous study . Rubinstein's study implied that after practitioners and medical institutions had achieved the upper limit of P4P indicators, their improvement for medical care quality would soon reach a plateau, which was called the ceiling effect . Serumaga and Fleetcroft reported that no more improvement did medical institutions accomplish for implementing the P4P after they had already reached the maximum threshold.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Once the upper limit of P4P indicators were achieved, practitioners and medical institutions can acquire the corresponding payment, then spare no more effort to enhance the quality of medical care continuously, suggesting a comprehensively modest improvement in part consistent with previous study . Rubinstein's study implied that after practitioners and medical institutions had achieved the upper limit of P4P indicators, their improvement for medical care quality would soon reach a plateau, which was called the ceiling effect . Serumaga and Fleetcroft reported that no more improvement did medical institutions accomplish for implementing the P4P after they had already reached the maximum threshold.…”
Section: Discussionsupporting
confidence: 66%
“…Thirteen focused on the preventive care , 10 of which reported the positive results in vaccine injection or screening of diseases such as cervical cancer screen. Twelve focused on the hypertension , 11 of which presented improvement on controlling the management of blood pressure. Fourteen related to coronary heart disease , and all got positive results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another before-and-after study, this one from Argentina, reported that P4P had no significant effect on patient satisfaction, due to a ceiling effect[69]. …”
Section: Resultsmentioning
confidence: 99%
“…In the UK (time-series study, 5 to 8% effect size)[35]; Spain (time-series study, above 30% effect size)[111]; and Argentina (before-and-after study, 5 to 30% effect size),[69] This arrangement seems to have reinforced the P4P effect, although one cannot be sure due to the lack of randomized studies with multiple control groups. In the USA, the impact of combined programs has been more mixed (mixed study designs, -11 to >30% effect size)[32-34,75,80,81,83,85,87,88,90,92,93,95,97-99,101-106,109,110,113-115].…”
Section: Resultsmentioning
confidence: 99%